Approximate Analytical Solutions Using Hyperbolic Functions for the Generalized Blasius Problem - Beong In Yun (Abstract and Applied Analysis)
We propose simple forms of approximate analytical solutions for the generalized Blasius problem based on the given boundary conditions and some known properties of the solution. The efficiency of the proposed solutions is shown for various cases. As a result, one can see that the solutions are uniformly accurate over the whole region.